Infant mortality in the Federal District, Brazil: time trend and socioeconomic inequalities Mortalidade infantil no Distrito Federal, Brasil: tendência temporal e desigualdades sócio-econômicas - Renata Alves Monteiro; Bethsáida de Abreu Soares Schmitz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
This study examined the trend in the infant mortality rate in the Federal District of Brazil (or Greater Metropolitan Brasilia, the national capital) from 1990 to 2000, analyzing the rate according to 5 administrative areas stratified by mean family income, from 1996 to 2000. An ecological time-series study was conducted using the Information Systems on Live Births and Mortality, produced by the Brazilian Ministry of Health. The infant mortality rate (IMR) decreased by 45.2% from 1990 to 2000, from 26.3 per 1000 live births to 14.4, or a mean annual reduction of 5.34% (R² = 0.9397; p < 0.0001). During this period there was a higher proportion of neonatal deaths. However, a higher percentage change occurred in the post-neonatal period (-59.0%, R² = 0.8452, p < 0.0001). Investigation of the IMR in the various areas of the Federal District showed a reduction in differences among the regions with respect to the component rates; however, substantial disparities persisted in relation to the income variable. The results suggest the need for effective interventions in the determinants of neonatal and post-neonatal mortality in order to improve maternal and infant health in all socioeconomic groups in the Federal District. O objetivo deste estudo é verificar a tendência da mortalidade infantil no Distrito Federal, Brasil, no período de 1990 a 2000 e descrevê-la, entre 1996 e 2000, nas cinco áreas do Distrito Federal estratificadas de acordo com a renda familiar média. Foi realizado um estudo ecológico de série temporal utilizando-se os Sistemas de Informação sobre Nascidos Vivos e Mortalidade produzidos pelo Ministério da Saúde. O coeficiente de mortalidade infantil (CMI) reduziu 45,2% entre 1990 e 2000, passando de 26,3 para 14,4 por mil nascidos vivos, sendo a taxa anual de decréscimo de 5,34% (R² = 0,9397; p < 0,0001). Ocorreu no período maior proporção de óbitos no período neonatal, porém, o maior decréscimo ocorreu no componente pós-neonatal (-59%, R² = 0,8452; p < 0,0001). Quando avaliado o CMI nas diversas áreas do Distrito Federal, observa-se que houve uma redução na diferença entre as regiões no que diz respeito a seus componentes, porém foram mantidas distorções importantes quanto à variável renda. Os resultados sugerem que há necessidade de intervenção efetiva nos determinantes da mortalidade infantil e seus componentes que resulte na melhoria da saúde materno-infantil em todos os grupos sócio-econômicos do Distrito Federal.